EVALUATION OF MUSCLE FUNCTION IN THE POSTOPERATIVE PERIOD OF LOWER LIMB TRAUMA AT A REFERRAL HOSPITAL FOR ORTHOPEDICS IN NORTH CENTRAL GOIÁS (CIPEEX, 2025)
Assessing muscle function aims to minimize possible complications and promote a more efficient recovery, allowing patients to return to their daily lives without significant changes. The aim of this study was to assess muscle function in the post-operative period of lower limb trauma surgery, carried out in an orthopedic referral hospital in the north-central region of Goiás. The research sought to understand the problems faced by patients who have undergone lower limb surgery and the challenges that can arise in the post-operative period. One of the studies investigated treatment with the Ilizarov method on lower limbs, which aimed to evaluate the load distributed on each limb with the method. Another study looked at limb salvage using flaps, with the aim of preserving functionality and reducing post-surgical complications. A third article compared the effects of early surgery and education on exercise and biomechanical symptoms. The methodology used included a review of articles in databases such as BVS and PubMed, focusing on publications from the last five years, in Portuguese and English. The following PICO descriptors were used: “lower extremity” AND “postoperative pain” OR “wounds and injuries” AND “assessment techniques” AND “musculoskeletal pain” AND “quality of life”. The results indicated a scarcity of research directly related to muscle function in postoperative patients. In the BVS, 109 articles were found, reduced to 31 after applying the filters. In PubMed, the total number of articles initially found was 600,329, but with the filters applied, 224,896 remained. However, no articles specific to the topic were found.
Keywords: lower extremity; postoperative pain; assessment techniques; musculoskeletal pain